2019
DOI: 10.1002/cssc.201901015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Effect of Oxygen Vacancies on the Electronic Structure and Pseudocapacitance of MnO2

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 58 publications
(87 reference statements)
3
30
0
Order By: Relevance
“…As shown in Figure 4(a), the Mn2p3/2 spectrum was deconvoluted into two peaks at 641.1 eV and 642.3 eV, while the Mn2p1/2 spectrum could be fitted into two peaks at 652.7 eV and 653.8 eV. The peaks at 641.1 eV and 652.7 eV are attributed to Mn 3+ ; while the peaks at 642.3 eV and 653.8 eV are attributed to Mn 4+ [22] . From the Mn2p spectrum the ratios of Mn 3+ /Mn 4+ were calculated and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 4(a), the Mn2p3/2 spectrum was deconvoluted into two peaks at 641.1 eV and 642.3 eV, while the Mn2p1/2 spectrum could be fitted into two peaks at 652.7 eV and 653.8 eV. The peaks at 641.1 eV and 652.7 eV are attributed to Mn 3+ ; while the peaks at 642.3 eV and 653.8 eV are attributed to Mn 4+ [22] . From the Mn2p spectrum the ratios of Mn 3+ /Mn 4+ were calculated and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the samples had a mixed valence state. Meanwhile, the Mn2p spectrum was used to estimate proportions of manganese in different valence states [22] . As shown in Figure 4(a), the Mn2p3/2 spectrum was deconvoluted into two peaks at 641.1 eV and 642.3 eV, while the Mn2p1/2 spectrum could be fitted into two peaks at 652.7 eV and 653.8 eV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations